1998
DOI: 10.1074/jbc.273.45.29489
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton Antigens Associated with IgE Antibodies and Delayed Type Hypersensitivity

Abstract: The dermatophyte fungus Trichophyton exhibits unique immunologic properties by its ability to cause both immediate and delayed type hypersensitivity. An 83-kDa Trichophyton tonsurans allergen (Tri t 4) was previously shown to elicit distinct T lymphocyte cytokine profiles in vitro. The homologous protein, Tri r 4, was cloned from a Trichophyton rubrum cDNA library, and the recombinant protein was expressed in Pichia pastoris. This 726-amino acid protein contained an arrangement of catalytic triad residues char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 47 publications
2
76
1
1
Order By: Relevance
“…Recombinantly expressed Tri r2 cannot be attributed enzymic activity on various protein substrates, but this antigen induced delayed type hypersensitivity (DTH) reactions and was the first known recombinant protein triggering both IgE antibody-and cell-mediated immune responses in humans (Woodfolk et al, 1998). Interestingly, DTH reactions are assumed to be associated with highly inflammatory skin lesions in dermatophytosis (for review see Woodfolk, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinantly expressed Tri r2 cannot be attributed enzymic activity on various protein substrates, but this antigen induced delayed type hypersensitivity (DTH) reactions and was the first known recombinant protein triggering both IgE antibody-and cell-mediated immune responses in humans (Woodfolk et al, 1998). Interestingly, DTH reactions are assumed to be associated with highly inflammatory skin lesions in dermatophytosis (for review see Woodfolk, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that the gene encoding the serine protease subtilisin Sub6, which was not detectably activated during in vitro growth on keratin, was the most upregulated host-specific A. benhamiae sequence. Interestingly, Sub6 has been previously identified as the major allergen Tri r2 in T. rubrum (Woodfolk et al, 1998). Besides SUB6, the closely related SUB7 as well as SUB1 and SUB2 were specifically upregulated in vivo.…”
Section: Differential Activation Of a Benhamiae Protease Genes Durinmentioning
confidence: 96%
“…However, studying cytokine production induced by whole Ag in T cell clones or lines does not provide insight into the diversity of T cell populations that constitute allergen-specific T cell repertoires. Cloning of Ags derived from Trichophyton rubrum has provided molecular tools for examining the T cell repertoire associated with distinct immune responses to Trichophyton (21). We recently reported major differences between IH and DTH responders in T cell repertoires specific for a 29-kDa allergen derived from T. rubrum, Tri r 2, which is a serine proteinase homologue (22).…”
Section: Haracterization Of Distinct Cd4mentioning
confidence: 99%
“…r-Tri r 2 (29 kDa) was produced in Escherichia coli strain BL21 as a GST fusion protein using the pGEX-4T-3 expression vector (21). rGST produced by the same method was used as a negative control in skin test and in vitro lymphocyte cultures.…”
Section: Preparation Of Ags and Peptidesmentioning
confidence: 99%
“…In M. canis, a three-member metalloprotease (fungalysin) gene family (Brouta et al, 2002) including the previously characterized 43?5 kDa protease (Brouta et al, 2001), as well as a subtilisin gene family (Descamps et al, 2002) including a previously characterized 31?5 kDa protease (Mignon et al, 1998), were identified. In T. rubrum, a single serine protease has been characterized at gene level (Woodfolk et al, 1998).…”
Section: Introductionmentioning
confidence: 99%